Fritz Hochwälders Großstadtroman «Donnerstag» oder Wie sich Schnitzler-Szenarien mit Horváth-Figuren erden lassen (Studia austriaca, 2012)
The 155 scenes of Fritz Hochwälder’s posthumous novel group around one central idea: each of the characters expects a final decision from the coming Thursday. What was read as a loosely connected series of expressionistic short scenes reveals itself as a carefully constructed whole. The narrative cement is provided by erotic relationships, by the visualization of metropolitan patterns of motion, and by a tightly woven texture of motives. Through emotional and economic treason, Hochwälder puts Schnitzler’s language of love in the mouths of characters from Horváth’s narrative worlds, and he exploits an up to now overlooked criminal plot.